Improving the Assessment of Interlaminar Shear strength for Composites - Fayad, Abdalhadi Mohammed Hasan (2025)
A Master of Science thesis in Mechanical Engineering by Abdalhadi Mohammed Hasan Fayad entitled, “Improving the Assessment of Interlaminar Shear strength for Composites”, submitted in December 2025. Thesis advisor is Dr. Maen Abdelqader Alkhader and thesis co-advisor is Dr. Bassam Abu-Nabah. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).